How does soil water status influence the fate of soil organic matter? A review of processes across scales - Védère, Charlotte; Lebrun, Manhattan; Honvault, Nicolas; Aubertin, Marie-Liesse; Girardin, Cyril; Garnier, Patricia; Dignac, Marie-France; Houben, David; Rumpel, Cornelia (Earth-science reviews, 2022)
Due to its influence on multiple soil processes, water intervenes in biogeochemical cycles at multiple spatial scales with contrasting effects on soil organic carbon (SOC) dynamics. On all scales, water availability influences biological processes, such as plant growth and (micro-)biological activity, leading to organic matter input, its decomposition and stabilisation. On the other hand, SOC influences soil hydrology via its impact on soil wettability and its structural organisation. Our objectives were to review the mechanisms involved in the complex relationship between water and SOC at different scales and to discuss levers of action to improve its modelling and management. We carried out a systematic review and synthesised the information of 987 articles dealing with SOC sequestration and soil water. At the landscape scale, precipitation levels influence vegetation type and biomass production as well as horizontal and vertical transport, determining SOC stocks and their spatial distribution. At the profile scale, SOC and water both control biological processes including those involved in soil aggregate formation, and organisation of soil porosity. Soil organic matter (SOM) decomposition and stabilisation processes occur at the microscale, where water movement facilitates the co-occurrence of SOM and microorganisms. All these multiscale processes may change the nature and distribution of SOM, leading to promotion or inhibition not only of biogeochemical cycling but also of the water cycle. Taking into account these mutual feedback mechanisms in mechanistic models requires their representation at multiple scales through developing modelling parameters in particular for microbial processes occurring in the pore space. This could greatly reduce modelling uncertainty and improve our understanding of global carbon cycling. Levers of action to improve soil water status and consequently SOC accrual include irrigation, and use of organic amendments. Sustainable agricultural practices should focus on (1) optimising the management of water resources and (2) choosing crop species adapted to various water levels to maintain and foster SOC sequestration, to adapt to climate change and in particular extreme events, such as drought and flooding.